Let's solve the equation step by step, filling in the missing terms as we go.
We start with the equation:
\[ \frac{c}{-5} - 10 = 5 \]
Step 1: Isolate the term with \( c \)
Add 10 to both sides:
\[ \frac{c}{-5} = 5 + 10 \]
Simplifying the right side gives:
\[ \frac{c}{-5} = 15 \]
Step 2: Solve for \( c \)
Now, multiply both sides by \(-5\):
\[ c = 15 \times -5 \]
Calculating that gives:
\[ c = -75 \]
So, the completed steps are:
- \(\frac{c}{-5} - 10 = 5\)
- \(\frac{c}{-5} = 15\) (after adding 10)
- \(c = -75\) (after multiplying by \(-5\))